Impaired Cognitive Flexibility in Amyotrophic Lateral Sclerosis. Issue 1 (March 2015) - Evans, Jessica; Olm, Christopher; McCluskey, Leo; Elman, Lauren; Boller, Ashley; Moran, Eileen; Rascovsky, Katya; Bisbing, Teagan; McMillan, Corey T.; Grossman, Murray
Abstract : Background and Objective: Up to half of patients with amyotrophic lateral sclerosis (ALS) may have cognitive difficulty, but most cognitive measures are confounded by a motor component. Studies relating impaired cognition in ALS to disease in gray matter and white matter are rare. Our objective was to assess executive function in patients with ALS using a simple, untimed measure with minimal motor demands, and to relate performance to structural disease. Methods: We gave the Visual-Verbal Test to 56 patients with ALS and 29 matched healthy controls. This brief, untimed measure of cognitive flexibility first assesses participants' ability to identify a feature shared by 3 of 4 simple geometric designs. The participants' cognitive flexibility is challenged when they are next asked to identify a different feature shared by another combination of 3 of the same 4 geometric designs. In a subset of 17 patients who underwent magnetic resonance imaging, regression analyses related test performance to gray matter atrophy and reduced white matter fractional anisotropy. Results: The patients with ALS showed significant impairment in cognitive flexibility ( P <0.01), with 48.2% making an error on the test. Regression analyses related impaired cognitive flexibility to gray matter atrophy in inferior frontal and insular regions, and to reduced fractional anisotropy in white matter projections in the inferior fronto-occipital and uncinate fasciculi and corpus callosum. Conclusions: Our patients with ALS had impaired cognitive flexibility on an untimed measure with minimal motor demands, a finding related in part to a large-scale frontal network that is degraded in ALS. Abstract : Supplemental Digital Content is available in the text.